(3GdHjGf aj cTa CSQGQ GdWH ddYjGfs - (3eMeO Hf CMeO Hf Ydj GdMehjs
(3ChdgG (B:s
(3CeG HYO(B: (3adeG QCjJ eG GTJed Ydjg ehdGfG YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd ef GbJfGA GdYdhe QCjJ Cf CNOe HGHg GdYGdj s
(3BNQgG (B:s
(3hjLYd Ydjg ef Ogf GdNQhY SHYI CQWGd hjWHN HfGQdjfI MJi jPgH GdeGA hjHbi GdOgf, hTQHJg eKbGdGf HeGA GdCUhd s
(3YdjgG JUMjMGJ hJedcGJs
(3CXgQgG Jedc HGSe jMjj Hf GdMSf Hf GdbGSe Hf Ydjs
(3hHYV cdeGJgG HGdMeQI hGdUaQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs